The p38 MAPK Inhibitor SB203580 Abrogates Tumor Necrosis Factor-Induced Proliferative Expansion of Mouse CD4+Foxp3+ Regulatory T Cells - He, Tianzhen; Liu, Shuoyang; Chen, Shaokui; Ye, Jingyi; Wu, Xueqiang; Bian, Zhaoxiang; Chen, Xin (Frontiers in Immunology, 2018)
There is now compelling evidence that tumor necrosis factor (TNF) preferentially activates and expands CD4+FoxP3+ regulatory T cells (Tregs) through TNF receptor type II (TNFR2). However, it remains unclear which signaling transduction pathway(s) of TNFR2 is required for the stimulation of Tregs. Previously, it was shown that the interaction of TNF-TNFR2 resulted in the activation of a number of signaling pathways, including p38 MAPK, NF-kappaB, in T cells. We thus examined the role of p38 MAPK and NF-kappaB in TNF-mediated activation of Tregs, by using specific small molecule inhibitors. The results show that treatment with specific p38 MAPK inhibitor SB203580, rather than NF-kappaB inhibitors (Sulfasalazine and Bay 11-7082), abrogated TNF-induced expansion of Tregs in vitro. Furthermore, up-regulation of TNFR2 and Foxp3 expression by TNF was also markedly inhibited by SB203580. The proliferative expansion and the up-regulation of TNFR2 expression on Tregs in LPS-treated mice were mediated by TNF-TNFR2 interaction, as shown by our previous study. The expansion of Tregs in LPS-treated mice were also markedly inhibited by in vivo treatment with SB203580. Taken together, our data clearly indicate that the activation of p38 MAPK is attributable to TNF/TNFR2-mediated activation and proliferative expansion of Tregs. Our results also suggest that targeting of p38 MAPK by pharmacological agent may represent a novel strategy to up- or down-regulation of Treg activity for therapeutic purposes.